Hormonal Therapy Treatment Pattern For Breast Cancer Patients At Dr. Moewardi Hospital, Surakarta - Luthfiyanti, Niken; Rohmana, Vivin Marwiyati; Khusain, Muhammad Fuad Zidane (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Breast cancer is a cancer with a high prevalence and mortality rate in women. One of the main therapies for hormone receptor-positive patients isAdjuvant Endocrine Therapy (AET) in the form of tamoxifen, either alone or in combination. The study aims to determine patient characteristics and patterns of hormonal therapy use.breast cancer patients at Dr. Moewardi Regional Hospital, Surakarta. The study used a randomized controlled study design.cross sectional with technique purposive samplingThe study subjects were 64 breast cancer patients undergoing tamoxifen therapy for at least one month. Data were obtained from medical records and questionnaires, then tested using Chi-Square see the relationship between variables. The results of the study showed that the majority of patients were aged <50 years (60.9%) and were in advanced stages (III–IV) at 57.8%. The most common type of therapy was a combination of chemotherapy and hormones (51.6%), while single hormonal therapy was used in 48.4% of patients. The most frequently used chemotherapy regimen was a combination of Cyclophosphamide & Epirubicin, while the most common hormonal therapy was Tamoxifen + Zoladex. Bivariate analysis showed a significant relationship between age and type of therapy and stage and type of therapy (p<0.05).